Implementasi Instrumen Penilaian Pembelajaran pada Anak Usia Dini di RA Sholahiyah Bae Kudus - Akbar, Rofiq Faudy; Ulumiyah, Miftakhul; Wirdah, Charissatul; Sulistiyaningrom, Ririn (Jurnal Raudhah, 2024)
Early childhood learning assessment is something that must be done by educators in every institution to determine children's development. This research focuses on assessing children aged 4-5 years in group A which refers to the independent curriculum implemented in one of the PAUD institutions, namely RA Sholahiyah Bae Kudus. This research aims to find out how learning assessment is implemented for children aged 4-5 years, the instruments used, and the obstacles and supporting factors at RA Sholahiyah Bae Kudus. This research uses qualitative methods using data collection techniques in the form of observation, interviews and documentation. The subjects of this research were the principal, class A1 and A2 teachers, employees and students aged 4-5 years at RA Sholahiyah Bae Kudus. This research uses the Miles and Huberman model where data analysis consists of data collection, data reduction, data presentation, and data withdrawal. The results of the research show that RA Sholahiyah Bae Kudus in implementing it used the independent curriculum as a reference using three assessment instruments including: anecdotal notes, checklists, and work results. The assessment process carried out by educators is by observing and analyzing each child according to learning activities, student needs and learning achievements. In this case there are also obstacles in the assessment process, but for every obstacle there is a way out through solutions or suggestions.